Femvertising Discourse: Empowering Women through Content Analysis in Du Anyam’s Instagram Marketing Campaign - Christanto, Yohanes Michael; Kartika, Lucia Nurbani (Integrasi Sains Media, 2025)
Advertising and marketing are powerful tools for influencing consumer behavior and shaping societal norms and perceptions. Historically, advertisements have perpetuated gender stereotypes, portraying men as dominant and rational while reducing women to passive, decorative roles. However, the emergence of femvertising—a blend of feminism and advertising—has shifted this narrative by promoting gender equality and women's empowerment. This study examines how Du Anyam’s Instagram marketing campaign employs multimodal discourse to challenge traditional gender roles and advocate for women’s empowerment in Indonesia. Utilizing a qualitative approach grounded in Multimodal Discourse Analysis (MDA), the research explores the interplay of visual, linguistic, and semiotic elements across selected Instagram content from May to June 2024. The findings reveal that Du Anyam strategically integrates cultural symbols, authentic storytelling, and pro-women messages to construct narratives celebrating female agency, resilience, and economic independence. Visual elements such as gestures, facial expressions, and traditional crafts are combined with empowering language to reinforce the brand’s commitment to social change. Furthermore, the study highlights how femvertising can simultaneously serve commercial interests and contribute to broader discourses on gender equality. By fostering authentic representation and cultural relevance, Du Anyam’s campaign demonstrates the potential of femvertising as a tool for brand differentiation and social impact.